EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSIPENGELUARAN KAS DENGAN APLIKASI SYSTEM APPLICATION AND PRODUCT IN DATA PROCESSING (SAP) DALAM RANGKAPENINGKATAN EFEKTIVITAS KINERJA (STUDI KASUS PADA SUBDIT TRESURI DAN PENGELOLAAN DANAPT. PELABUHAN INDONESIA III (PERSERO) KANTOR PUSAT) - Adrian, Aldrin Johan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The aim of this study is to evaluate the application of a cash expenditureaccounting information system with SAP as conducted by the PT. PelabuhanIndonesia III (Persero) Head Office, especially in the Sub-Directorate ofTreasury and Fund Management, in order to improve performanceeffectiveness. This research is a qualitative study using a case study. Datawas obtained by conducting observations, documentation, and interviews.The utilized analysis technique of this study was descriptive analysis byidentifying the main components of the cash expenditure accountinginformation system, internal control of cash expenditure accountinginformation system, and comparing the theories with the practices thatoccur in the field. The results of the analysis showed that the implementedcash expenditure accounting information system with SAP had not beeneffective and efficient. This is seen in the incompatibility of internal controlsin the division of tasks between cash functions and accounting functions.From the results of the analysis, it is recommended that the companyimplement strategies that can be used to improve the effectiveness of itsperformance.Keywords:Accounting information system, cash expenditure.